FACTORS AFFECTING THE EVENT STUNTING IN TOLLS AT SEI BAMBAN HEALTH CENTER BATANG SATAN DISTRICT LANGKAT DISTRICT YEAR 2020 - Pangaribuan, Ingka Kristina; Said, Faridah Mohd; Dewi, Eva Ratna; Siahaan, Nadia; Simbolon, Marlina Lasmawati (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
The term “stunting” has become widespread in research, programs and international child health and nutrition policy circles. Stunting (short body) describes the condition of malnutrition that has been long since 1000 days of birth of a baby and it takes time for the child to develop and return to normal according to the growth and development of the child's age. This study aims to determine the factors that influence the incidence of stunting in toddlers at the Sei Bamban Health Center, Batang Serangan District, Langkat Regency in 2020. This research is an analytical survey with a cross sectional study design. The sampling technique was Simple Random Sampling with a total population of 20 children at the Puskesmas Sei Bamban. The method of collecting data for maternal nutrition variables during pregnancy, exclusive breastfeeding, complete basic immunization and environmental sanitation was using a questionnaire. Data analysis using Chi Square. The results showed that from 20 samples, 75.5% of children under five were stunted, 80.0% of mothers had a history of poor nutrition during pregnancy, 70.0% of children under five had a history of not exclusive breastfeeding, 45.0% of children under five received complete basic immunization. , and 85.0% have poor environmental sanitation. Meanwhile, complete basic immunization did not have a significant relationship with the incidence of stunting. Research suggests that the active role of the government, especially health workers, is to tackle the incidence of stunting in toddlers. In addition, it is hoped that the community will adopt a balanced nutrition diet to improve welfare